1992
DOI: 10.1152/ajprenal.1992.263.4.f594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and salt on rat renal osmolytes: covariation in urea and GPC contents

Abstract: Renal medullary cells contain high levels of (glycine) betaine, glycerophosphorylcholine (GPC), myo-inositol, and sorbitol. Two functions of these have been proposed: 1) that they are compatible osmolytes which regulate cell volume (against high external NaCl) without inhibiting proteins and 2) that methylamines (GPC and betaine) are counteracting osmolytes which stabilize proteins against perturbation from high renal urea. As a test of the latter, osmolyte contents in kidney medullas were measured in rats sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…This supports the findings of Bock et al (2004), who demonstrated that 40 g head/day of betaine supplemented to beef steers consuming pasture for 7 days pre-slaughter improved carcass weight, although this was not the case for steers supplemented with dietary betaine while in the feedlot. Betaine can reduce maintenance energy requirements (Schrama et al 2003) by reducing ion pumping associated with maintaining cellular osmolarity (Nakanishi et al 1990;Lohr et al 1991;Peterson et al 1992), and in cattle betaine is lipotropic and may increase fat thickness (Bock et al 2004;Loest et al 2002), as somewhat supported by the results of the present experiment in the P8 backfat responses to the 10 g dose. Thus, the trend for carcass weight to be increased in steers supplemented with betaine may be the result of increased fat thickness.…”
Section: Discussionsupporting
confidence: 73%
“…This supports the findings of Bock et al (2004), who demonstrated that 40 g head/day of betaine supplemented to beef steers consuming pasture for 7 days pre-slaughter improved carcass weight, although this was not the case for steers supplemented with dietary betaine while in the feedlot. Betaine can reduce maintenance energy requirements (Schrama et al 2003) by reducing ion pumping associated with maintaining cellular osmolarity (Nakanishi et al 1990;Lohr et al 1991;Peterson et al 1992), and in cattle betaine is lipotropic and may increase fat thickness (Bock et al 2004;Loest et al 2002), as somewhat supported by the results of the present experiment in the P8 backfat responses to the 10 g dose. Thus, the trend for carcass weight to be increased in steers supplemented with betaine may be the result of increased fat thickness.…”
Section: Discussionsupporting
confidence: 73%
“…and trophosome (Troph., location of sulfide-oxidizing microbial symbionts), which also has high levels of thiotaurine; (6) mammalian renal cells (inner medulla) have varying levels of sorbitol, myo-inositol, GPC, betaine and taurine (along with urea). Data from Peterson et al (1992); Yin et al (2000); Yancey et al (2002); Fiess et al (2002); Rosenberg et al (2003).…”
Section: Types Of Organic Osmolytesmentioning
confidence: 99%
“…As another example, the mammalian renal medulla appears to regulate one of its methylamine osmolytes, GPC, to maintain a constant ratio to urea, rather than for osmotic stress alone (Peterson et al, 1992). Again, if this methylamine is a simple compatible solute, why not use it at high levels under all water-stress conditions?…”
Section: Mechanisms Of Stabilizationmentioning
confidence: 99%
“…Medullary cells, which often have high urea content as a result of the urinary concentrating mechanism, have close to a 2:1 ratio of urea to the methylamines glycerophosphorylcholine (GPC) and betaine ( Fig. 1), with GPC regulated in parallel with urea (Peterson et al, 1992). These methylamines can counteract the effects of urea on proteins (Burg et al, 1996).…”
Section: Osmolyte Properties: Inorganic Ions Versus Compatible Solutesmentioning
confidence: 99%